187k views
15 votes
Which expressions are equivalent. Circle your answer.

a. 10x - 6x
b. 7x + 3x
C. 12x + 2x - 10x
d. X - X + 2x

User Mesop
by
4.9k points

2 Answers

13 votes

Answer:

Options A and C

Solution:

  • In order to simplify these expressions, we should combine like terms:
  • 10x-6x=4x
  • 7x+3x=10x
  • 12x+2x-10x=14x-10x=4x (so expressions A & C are equivalent)
  • x-x+2x=0x+2x=2x

Hope it helps.

Do comment if you have any query.

User Bryan Edds
by
5.3k points
9 votes

Answer: a) 10x-6x and c) 12x+2x-10x

Explanation:

Lets start by simplifying all the expressions

a) 10x-6x=4x

b)7x+3x=10x

c)12x+2x-10x=14x-10x=4x

d)x-x+2x=2x

As you can see a and c both simplify to 4x meaning that is our answer.

User Undershock
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.